Role of Supportive Leadership as a Moderator between Job Stress and Job Performance - Khalid, Afsheen; ., Aliya Zafar; ., Mueen Aizaz Zafar; ., Lutfullah Saqib; ., Rizwan Mushtaq (Information Management and Business Review, 2012)
Stress is a major problem faced by employees in the working environment that affects performance. This problem can be resolved if employees receive support from their leaders. This study was conducted to examine the moderating effect of supportive leadership on the relationship between job stress and job performance. Supportive leadership is an important factor enhancing employee performance in organizations. In this research, 200 employees were considered from 4 educational institutions. Data was collected using a well-developed questionnaire. The empirical results reveal that supportive leadership has a negative effect on job stress and directly impacts job performance. The study also revealed that Supportive Leadership moderates the relationship between these constructs. The paper concludes with recommendations for further research.